Agraphs: definição, implementação e suas ferramentas - Sena, Demóstenes Santos de (2006)
Programs manipulate information. However, information is abstract in nature and needs to be represented, usually by data structures, making it possible to be manipulated. This work presents the AGraphs, a representation and exchange format of the data that uses typed directed graphs with a simulation of hyperedges and hierarchical graphs. Associated to the AGraphs format there is a manipulation library with a simple programming interface, tailored to the language being represented. The AGraphs format in ad-hoc manner was used as representation format in tools developed at UFRN, and, to make it more usable in other tools, an accurate description and the development of support tools was necessary. These accurate description and tools have been developed and are described in this work. This work compares the AGraphs format with other representation and exchange formats (e.g ATerms, GDL, GraphML, GraX, GXL and XML). The main objective this comparison is to capture important characteristics and where the AGraphs concepts can still evolve